Level of Sustainability Heritage Cities in Malaysia (Sains Humanika, 2022)
This article aims to measure the level of sustainability of heritage cities in Malaysia. Respondents consisted of 1000 residents in 10 selected heritage towns throughout Malaysia selected based on cluster sampling method and simple random to fill out a questionnaire. Likert scale questionnaires 1 to 5 were used to elicit feedback. Five sustainability constructs were used, namely economic, social, environmental, cultural heritage, and government/community role. The results showed that items in each study construct achieved acceptable reliability with a Cronbach Alpha value greater than 0.70 and met normality test requirements. Descriptive analysis of frequency, percentage, and mean values were used to obtain each construct's level of sustainability. The results of the study found that the cities that got high scores were Georgetown (3.94), Taiping (4.00), Melaka City (3.76), and Muar (3.71). Meanwhile, the cities that got average scores were Kuala Kubu Bharu (3.36), Jugra (3.23), Tampin (3.37), Kuala Lipis (3.28), Kota Bharu (3.65), and Kuching (3.51). Only, five cities surpass the average value of Malaysia heritage cities of 3.58. The implications of this study can be used as an indicator of the level of sustainability of heritage cities in Malaysia and be a reference to make the process of improvement towards a more sustainable city by 2030.
Keywords: heritage city, sustainability level, sustainability construct, cultural heritage